A literatura afro-brasileira: pela descolonização do ensino de literatura - Loyola, Emanuelle Rodrigues (2019)
This dissertation conducts the study of female Afro-Brazilian literature in high school as a decolonial pedagogical practice that leads the student to a reflection on the current colonizing models, renouncing the unique forms of knowledge, society and culture, as well as their forms of validation. to make room for diversity and sociocultural plurality, in line with Law 10.639 / 03 which provides for the study of African and Afro-Brazilian history and literature at school. It starts from the line of thought of Candido (2011), who thinks literature as a transforming factor of man as a humanizing act. Afro-Brazilian literature in the classroom breaks with the canonical molds and allows the reader a social construction of respect and knowledge of the other and the reconstruction of an individual and collective identity, making room for the voice and female black authorship. For this, the study makes a historical survey of the literature in education in Brazil, observing how was the teaching of literature and how the official documents of the MEC, after the approval of LDB nº. 9394/96 and its modifications from the law. 10.639 / 03 have generated other forms and appreciations of the literary text in the classroom. It used an action research through reading workshops developed with students of the second year of high school electing the Afro-Brazilian tales of Conceição Evaristo and Fátima Trinchão for reading and following the proposal of the basic sequence of literary literacy by Rildo Cosson. It was analyzed the reception of these texts and how the elements present in Afro-Brazilian literature, memory, ancestry, orality, are noticed by the students, from a literary practice that leads to aesthetic and reflective contact.